Data Analytics for Renewable Energy Integration Third ECML PKDD Workshop, DARE 2015, Porto, Portugal, September 11, 2015. Revised Selected Papers - Woon, Wei Lee; Aung, Zeyar; Madnick, Stuart (Lecture Notes in Artificial Intelligence, 2015)
This book constitutes revised selected papers from the third ECML PKDD Workshop on Data Analytics for Renewable Energy Integration, DARE 2015, held in Porto, Portugal, in September 2015. The 10 papers presented in this volume were carefully reviewed and selected for inclusion in this book.